2018
DOI: 10.3892/ol.2018.8790
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of XAV939 on the proliferation of small‑cell lung cancer H446 cells and Wnt/β‑catenin signaling pathway in�vitro

Abstract: Lung cancer, including small-cell lung carcinoma (SCLC) and non-small cell lung carcinoma (NSCLC), are the most common tumor types, which represent 13% of newly diagnosed cancer cases worldwide. SCLC represents 15% of all lung cancer cases. Although an increasing number of novel targeted drugs are employed for the treatment of NSCLC, including Iressa, Tarceva and Conmana, there have been almost no major breakthroughs in SCLC over the last 30 years. Therefore, new drug targets are required to treat or prevent S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…XAV939 was characterized as a small molecule inhibitor of Wnt signalling pathway, which could block Wnt signalling in cancer cell lines through binding to tankyrase (TNKS) catalytic poly-ADP-ribose polymerase (PARP) domain, in turn, results in dramatic stabilization of the Axin protein, thereby leads to inhibition of transcription regulated by b-catenin [24,25]. Besides, compared with other Wnt pathway inhibitors, XAV939 has a strong specificity for the Wnt signalling pathway without affecting NF-jB or TGF-b signalling pathways [22].…”
Section: Introductionmentioning
confidence: 99%
“…XAV939 was characterized as a small molecule inhibitor of Wnt signalling pathway, which could block Wnt signalling in cancer cell lines through binding to tankyrase (TNKS) catalytic poly-ADP-ribose polymerase (PARP) domain, in turn, results in dramatic stabilization of the Axin protein, thereby leads to inhibition of transcription regulated by b-catenin [24,25]. Besides, compared with other Wnt pathway inhibitors, XAV939 has a strong specificity for the Wnt signalling pathway without affecting NF-jB or TGF-b signalling pathways [22].…”
Section: Introductionmentioning
confidence: 99%
“…22 XAV939 is a small molecule inhibitor of dysregulated Wnt signaling pathway. 23 Researchers found that XAV939 could inhibit the growth of non-small cell lung cancer cells by blocking the Wnt signaling pathway. 23 Another study also discovered that XAV939 inhibited the proliferation and migration of A549 cells via WNT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…23 Researchers found that XAV939 could inhibit the growth of non-small cell lung cancer cells by blocking the Wnt signaling pathway. 23 Another study also discovered that XAV939 inhibited the proliferation and migration of A549 cells via WNT pathway. 21 Western blot data demonstrated that β-catenin expression in XAV939 treatment groups (2μM) was decreased remarkably, compared with the GOLPH3 or Cis group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we did not observe any effect of XAV939 on TGF-β induced EMT in NMuMG cells, despite the fact that TNKS inhibition by XAV939 and the subsequent modulation of WNT pathway inhibits the proliferation of small-cell lung cancer H446 cells as well as proliferation and migration of lung adenocarcinoma A549 cells [47,48].…”
Section: Discussionmentioning
confidence: 99%